Development and Application of a Multi-Residue Method to Determine Pesticides in Agricultural Water Using QuEChERS Extraction and LC-MS/MS Analysis - Nho-Eul Song; Young Sung Jung; Ji Yeon Choi; Minseon Koo; Hyo-Kyoung Choi; Dong-Ho Seo; Tae-Gyu Lim; Tae Gyu Nam (Separations, 2020)
Agricultural water is closely linked to surface and ground water as well as soil; hence, ensuring its safety is an important endeavor. We used the “quick, easy, cheap, effective, rugged, and safe” (QuEChERS) method to analyze multi-residue pesticides in agricultural water by using a combined-sorbent-based clean-up procedure. Among the various sorbents examined, clean-up using ENVI-Carb combined with a primary secondary amine sorbent delivered the highest recovery of multi-residue pesticides (>93.9%). While the developed method showed satisfactory linearity (R2 > 0.9991), precision, and specificity, recovery was low for pyrazolate (29.1%) and thidiazuron (59.2%). The limits of detection and quantification for the 55 pesticides targeted in this study were in 0.02–3.0 μg L−1 and 0.1–9.9 μg L−1, respectively. The developed method was used to identify and quantify multi-residue pesticides during sample analysis. The results suggest that the QuEChERS method employing a combination of ENVI-Carb and another sorbent can be applied for the effective analysis of multi-residue pesticides in agricultural water.